Analisis Maqāṣid al-sharī’ah dalam Transaksi Jual Beli Ornamen Keagamaan Nonmuslim - Rayyahun, Annisa; Sabbar, Sabbar Dahham (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
This research examines the maqāṣid al-sharī’ah perspective in the context of buying and selling non-Muslim religious ornaments with a contemporary fiqh muamalah approach. The main focus of the research is to analyze the legal aspects, limitations, and implications of the transaction within the framework of maintaining the five fundamental aspects (ḍarūriyyah al-khams). The research methodology uses a qualitative approach with descriptive-normative analysis, combining classical and contemporary literature studies, as well as comparative analysis of scholarly opinions. Primary data is obtained from classical fiqh books, fatwas of contemporary scholars, and documentation related to the practice of buying and selling religious ornaments. Secondary data includes journals, scientific articles, and related research results. The results of the study show that: First, there are variations of scholarly opinions in determining the law of buying and selling non-Muslim religious ornaments. Second, this practice is permissible as long as it does not violate sharia principles, such as supporting activities that are contrary to Islam or harming the ummah. This transaction must maintain maslahat, tolerance and social harmony without obscuring Islamic identity.